Employment effects of welfare reforms: evidence from a dynamic structural life-cycle model - Peter Haan; Victoria Prowse; Arne Uhlendorff (Institute for the Study of Labor (IZA), 2008)
In this paper we develop a dynamic structural life-cycle model of labor supply behavior which fully accounts for the effect of income tax and transfers on labor supply incentives. Additionally, the model recognizes the demand side driven rationing risk that might prevent individuals from realizing their optimal labor supply state, resulting in involuntary unemployment. We use this framework to study the employment effects of transforming a traditional welfare state, as is currently in place in Germany, towards a more Anglo-American system in which a large proportion of transfers are paid to the working poor.
urn:nbn:de:101:1-2008052708
Keywords: J22; 330; Life-cycle labor supply; involuntary unemployment; in-work credits; Sozialreform; Aktivierende Sozialhilfe; Wirkungsanalyse; Beschäftigungseffekt; Arbeitsangebot; Ökonomischer Anreiz; Lebenszyklus; Einkommensteuer; Sozialtransfer; Unfreiwillige Arbeitslosigkeit; Theorie; Deutschland